Leksikon Flora dan Fauna dalam Kumpulan Cerita Rakyat Kabupaten Kuningan: Kajian Ekolinguistik - Dewi, Figiati Indra; Suntini, Sun; Hanifah, Ifah (Ideas Publishing, 2024)
Kuningan Regency has a variety of folktales that illustrate closeness to nature. From this background, this study aims to identify the flora and fauna lexicon in a collection of folktales of Kuningan Regency and its morphological process. The method used is descriptive qualitative by using the theory of ecolinguistics and morphological process. The results showed that the types of flora and fauna consisted of (1) flora lexicons such as tamiyang 'small bamboo tree', tangkal ki lampayan 'jelutang tree', and so on; and (2) fauna lexicons such as lauk menga 'menga fish', kidang 'deer', and so on. The morphological process of all these lexicons is basic form, composition, reduplication, and affixation.